The Functional Polymorphism of DDAH2 rs9267551 Is an Independent Determinant of Arterial Stiffness - Averta, Carolina; Mancuso, Elettra; Spiga, Rosangela; Miceli, Sofia; Succurro, Elena; Fiorentino, Teresa Vanessa; Perticone, Maria; Mannino, Gaia Chiara; Thamtarana, Prapaporn Jungtrakoon; Sciacqua, Angela; Sesti, Giorgio; Andreozzi, Francesco (Frontiers in Cardiovascular Medicine, 2022)
Background: The association of circulating asymmetric dimethylarginine (ADMA) levels with cardiovascular risk and arterial stiffness has been reportedly demonstrated, although the causal involvement of ADMA in the pathogenesis of these conditions is still debated. Dimethylaminohydrolase 2 (DDAH2) is the enzyme responsible for ADMA hydrolysis in the vasculature, and carriers of the polymorphism rs9267551 C in the 5′-UTR of DDAH2 have been reported to have higher DDAH2 expression and reduced levels of serum ADMA. Approach and Results: We genotyped rs9267551 in 633 adults of European ancestry and measured their carotid–femoral pulse wave velocity (cfPWV), the gold-standard method to estimate arterial stiffness. cfPWV resulted significantly lower in rs9267551 C allele carriers (Δ = −1.12 m/s, P < 0.01) after correction for age, sex and BMI, and a univariate regression showed that the presence of rs9267551 C variant was negatively associated with cfPWV (β = −0.110, P < 0.01). In a multivariable regression model, subjects carrying the rs9267551 C allele manifested significantly lower cfPWV than GG carriers (β = −0.098, P = 0.01) independently from several potential confounders. We measured circulating ADMA levels in a subset of 344 subjects. A mediation analysis revealed that the effect of DDAH2 rs9267551 genotype on cfPWV was mediated by the variation in ADMA levels. Conclusions: These evidences hint that the presence of rs9267551 C allele may explain, at least in part, a reduction in vessel rigidity as measured by cfPWV, and support the attribution of a causative role to ADMA in the pathogenesis of arterial stiffness.